2008
DOI: 10.1007/s10995-008-0362-0
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and Obesity Among School Children in Jordan: Prevalence and Associated Factors

Abstract: While the prevalence of overweight was high among Jordanian children compared with that in the neighboring countries, the prevalence of obesity was lower.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
69
3
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 38 publications
17
69
3
5
Order By: Relevance
“…As regards the prevalence of overweight among school children in the Arab countries, our results are consistent with [9] and [10] in Saudi, [11] in Jordan and [12] in Qatar. On the other hand, our results were much lower than [13] in Kuwait.…”
Section: Discussionsupporting
confidence: 87%
“…As regards the prevalence of overweight among school children in the Arab countries, our results are consistent with [9] and [10] in Saudi, [11] in Jordan and [12] in Qatar. On the other hand, our results were much lower than [13] in Kuwait.…”
Section: Discussionsupporting
confidence: 87%
“…The growing epidemic of childhood obesity is a major public health concern, given that paediatric obesity has been shown to track into adulthood and predict a broad range of metabolic and psychological adverse health effects (152,153). Studies of the association of childhood obesity with socioeconomic, dietary and lifestyle factors have highlighted the following risk factors: higher socioeconomic status (154,155); urban residence (156); parental obesity (154,157), maternal BMI (155,158); television viewing (154); high sugar intake (155); high fat intake (155,156); high frequency of consumption of sugar-sweetened beverages and of fast foods (156,159); low consumption of vegetables, fruit and dairy products (156); and high frequency of eating out (156,160). Given the established link between paediatric obesity, the consumption of high-energy, high-sugar, high-fat foods and the marketing of such foods to children, the WHO Regional Office for the Eastern Mediterranean Region has recently released a regional nutrient profiling model designed for use by governments for the purposes of restricting food marketing to children (161).…”
Section: Discussionmentioning
confidence: 99%
“…Another study was done on 1072 children in Saudi Arabia, 14.9% out of them were obese, 95% of the obese children having high family income [9]. A Jordanian study was done on 2131 children; it reported a significant relation between obesity and being overweight with high family income in 19.4% and 5.6% respectively [10]. On the other hand, a study conducted in United State of America showed that family income and childhood obesity are negatively correlated in general, as for children in very low-income families are positively correlated and significant among high-BMI children [11].…”
Section: Discussionmentioning
confidence: 99%